2023
DOI: 10.1021/acssensors.2c02696
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Microfluidic Devices for Sample Preparation of Undiluted Whole Blood to Enable the Detection of Biomarkers

Abstract: Blood testing allows for diagnosis and monitoring of numerous conditions and illnesses; it forms an essential pillar of the health industry that continues to grow in market value. Due to the complex physical and biological nature of blood, samples must be carefully collected and prepared to obtain accurate and reliable analysis results with minimal background signal. Examples of common sample preparation steps include dilutions, plasma separation, cell lysis, and nucleic acid extraction and isolation, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…Outlet 3 was able to increase the concentration of blood cells threefold, from 5.78 × 10 8 to 1.73 × 10 9 cells/mL (Figure D). Meanwhile, the number of cells per ml exported from outlet 1 decreased by a factor of 10,000, which is technically over the current microfluidic chips. The study also found that the separation effect was better with higher dilutions (Figure E).…”
Section: Resultsmentioning
confidence: 80%
“…Outlet 3 was able to increase the concentration of blood cells threefold, from 5.78 × 10 8 to 1.73 × 10 9 cells/mL (Figure D). Meanwhile, the number of cells per ml exported from outlet 1 decreased by a factor of 10,000, which is technically over the current microfluidic chips. The study also found that the separation effect was better with higher dilutions (Figure E).…”
Section: Resultsmentioning
confidence: 80%
“…The system we have developed can be used for immediate diagnosis, home monitoring at a very low cost, and also applied in areas lacking medical resources and trained technicians (Table S2). Not only can it replace the microhematocrit centrifuge, we expect this device can be expanded to other clinical diagnostic applications with this modality or its modifier in monitoring other hematological health conditions. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it plays a crucial role in a variety of illnesses, including malaria, sickle cell anemia, and diabetes. , The intricate composition of blood encompasses plasma, erythrocytes (red blood cells), leukocytes (white blood cells), and thrombocytes (platelets). Erythrocytes constitute roughly 45% of the total blood volume, whereas leukocytes and platelets combined contribute to a comparatively minimal 1%. , 55% of the blood volume is constituted by plasma, a pale-yellow liquid. Its composition predominantly includes water, accounting for approximately 91%.…”
Section: Introductionmentioning
confidence: 99%
“…Its composition predominantly includes water, accounting for approximately 91%. Proteins contribute to 7% of the plasma content, while the residual 2% consists of inorganic ions and various other organic substances. Biomarkers within human plasma, such as proteins, electrolytes, urea, and glucose, provide a comprehensive overview of the body’s physiological state. With the advancements in the study of plasma proteomics, transcriptomics, and metabolomics, these biological markers play a significant analytical role in the diagnosis of various diseases. Similarly, the detection of antibodies, foreign nucleic acids, and antigens in blood plasma can be of great help in diagnosing serious infectious diseases, including Ebola Hemorrhagic Fever, Acquired Immune Deficiency Syndrome (AIDS), and the recent Coronavirus Pneumonia outbreak. However, the excessive presence of blood cells, especially platelets, can significantly disrupt the accurate identification of desired biomarkers in the bloodstream. Therefore, the process of extracting purer plasma by eliminating blood cells emerges as an imperative step. , …”
Section: Introductionmentioning
confidence: 99%